Comprehensive Assessment of Replication Dynamics and Characteristics in Wild Type and Corresponding Defective HBV DNA Stains - Zahir, Jawad; Sabir, Ali; Haseeb ur Rahman; Bukhari, Syed Ali; Muhammad Naeem; Nisa, Iqbal; Sana, Wasfa; Raihan, Madeeha; Younas, Itezaz (Indus Journal of Bioscience Research, 2024)
Hepatitis B virus (HBV) is a significant global health concern, requiring a deeper understanding of its replication and pathogenic mechanisms to develop effective therapies. This study investigated the transcription efficiency, antigen dynamics, and virion production of wild-type HBV (wtHBV) and defective HBV (dHBV) constructs. The levels of dHBV prRNA were 2.5 times higher in Sample 1 than in Sample 2. They were 2.8 times higher (p < 0.01) in Sample 2, even though the levels of cccDNA were the same in both samples (p > 0.25 for Sample 1 and p > 0.16 for Sample 2). The amount of transcription in dHBV improved considerably, as shown by the evidence that Sample 1 grew up three times and Sample 2 went up two times (p < 0.01). An examination of antigen dynamics showed that dHBV had less production of HBsAg and HBeAg but more storage of these two antigens in cells. The total concentrations of HBsAg inside cells were 2.5 to 3 times higher (p < 0.01), and the quantity of HBeAg also increased by the same amount over the course of the study. A new test was used to measure the number of HBV virions, and it was very sensitive and specific. Also, only 20–100 µL of supernatant was sufficient. The experiments showed that lamivudine inhibited virion secretion at concentrations ranging from 1 µM to 5 µM, and that across dilutions ranging from 1:2 to 1:20, there was an associated decrease in virion levels. There were approximately 0.5 million virions per millilitre in the serum samples, but no virions were found in the dHBV constructs. The findings show that dHBV may be competent to avoid detection and remain in the immune system due to its altered antigen dynamics and improved transcriptional pathways. This work offers a reliable tool for enhancing research on antiviral medicines and sheds light on the biology of HBV.